Saddle-induced erectile dysfunction. Fact or fiction? - Norvell, D.; Dettori, J. (Bicycle Paper, 1999)
While preliminary data seem to suggest their may be a link between bicycle riding and Erectile Dysfunction, we don't feel enough science exists to confidently claim you are at risk of ED if you continue to ride the standard saddle. If we don't know there is truly a problem than we certainly don't know if the answer lies in the "perfect" saddle.